Analisis Perbedaan Tarif Pelayanan Rumah Sakit Dengan Tarif INA-CBGs Pada Rsia Permata Hati Lotim - Lauza Agisni Zahara; Baiq Ulaya Fitriani; Bambang (Jurnal Riset Mahasiswa Akuntansi, 2025)
This study aims to analyze the magnitude and characteristics of the difference between the actual rates for delivery services and the INA-CBG's tariffs at RSIA Permata Hati in East Lombok. It also seeks to identify the factors causing these tariff differences and problematic BPJS receivables, evaluate the hospital's claims and receivables management efforts, and analyze the practical application of SAK EP (Private Entity Accounting Standards), particularly Chapter 23 concerning Revenue from Contracts with Customers, Chapter 4 concerning the Statement of Financial Position, and concerning management of BPJS receivables. The research employs a case study approach with both quantitative and qualitative methods, using delivery service claims data from February to December 2024. The findings indicate that the majority of claims result in a negative difference, where the hospital's actual costs exceed the INA-CBG's tariffs. The primary contributing factors include incomplete documentation, non-compliance of medical procedures with standards, and diagnostic inaccuracies. RSIA Permata Hati has undertaken various measures to improve its claims management and has begun implementing SAK EP, though it faces challenges in estimating the allowance for credit losses for the complex BPJS receivables.